TI_GERICHTE 11.2009.104 vom 3. Mai 2011 , Comproprietà: richiesta intesa a ottenere atti di amministrazione necessari - TI Tribunale d'appello (2011)
Comproprietà: richiesta intesa a ottenere atti di amministrazione necessari